Sustained Baclofen-Induced Activation of GABAB Receptors After Cerebral Ischemia Restores Receptor Expression and Function and Limits Progressing Loss of Neurons - Hleihil, Mohammad; Vaas, Markus; Bhat, Musadiq A.; Balakrishnan, Karthik; Benke, Dietmar (Frontiers in Molecular Neuroscience, 2021)
One important function of GABAB receptors is the control of neuronal activity to prevent overexcitation and thereby excitotoxic death, which is a hallmark of cerebral ischemia. Consequently, chronic activation of GABAB receptors with the selective agonist baclofen provides neuroprotection in in vitro and in vivo models of cerebral ischemia. However, excitotoxic conditions severely downregulate the receptors, which would compromise the neuroprotective effectiveness of baclofen. On the other hand, recent work suggests that chronic activation of GABAB receptors stabilizes receptor expression. Therefore, we addressed the question whether chronic activation of GABAB receptors reduces downregulation of the receptor under excitotoxic conditions and thereby preserves GABAB receptor-mediated inhibition. In cultured neurons subjected to oxygen and glucose deprivation (OGD), to mimic cerebral ischemia, GABAB receptors were severely downregulated. Treatment of the cultures with baclofen after OGD restored GABAB receptor expression and reduced neuronal death. Restoration of GABAB receptors was due to enhanced fast recycling of the receptors, which reduced OGD-induced sorting of the receptors to lysosomal degradation. Utilizing the middle cerebral artery occlusion (MCAO) mouse model of cerebral ischemia, we verified the severe downregulation of GABAB receptors in the affected cortex and a partial restoration of the receptors after systemic injection of baclofen. Restored receptor expression recovered GABAB receptor-mediated currents, normalized the enhanced neuronal excitability observed after MCAO and limited progressive neuronal death. These results suggest that baclofen-induced restoration of GABAB receptors provides the basis for the neuroprotective activity of baclofen after an ischemic insult. Since GABAB receptors regulate multiple beneficial pathways, they are promising targets for a neuroprotective strategy in acute cerebral ischemia.